2020
DOI: 10.1371/journal.ppat.1008717
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic evidence for descent from Plasmodium and loss of blood schizogony in Hepatocystis parasites from naturally infected red colobus monkeys

Abstract: Hepatocystis is a genus of single-celled parasites infecting, amongst other hosts, monkeys, bats and squirrels. Although thought to have descended from malaria parasites ( Plasmodium spp.), Hepatocystis spp. are thought not to undergo replication in the blood–the part of the Plasmodium life cycle which causes the symptoms of malaria. Furthermore, Hepatocystis is transmitted by biting midges, not mosquitoes. C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 118 publications
(188 reference statements)
4
36
1
Order By: Relevance
“…P22 is highly conserved among Plasmodium species (Figure S1B). BLAST search also identified a homologue of this protein in Hepatocystis , which is considered to be descended from Plasmodium with the loss of blood schizogony (Aunin et al, 2020). Transcriptomic analysis of asexual stages and separated male and female gametocytes showed that pb22 is expressed in both asexual stages and gametocytes, while in gametocytes pb22 expression level is about five times higher in female than male gametocytes (Yeoh, Goodman, Mollard, McFadden, & Ralph, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…P22 is highly conserved among Plasmodium species (Figure S1B). BLAST search also identified a homologue of this protein in Hepatocystis , which is considered to be descended from Plasmodium with the loss of blood schizogony (Aunin et al, 2020). Transcriptomic analysis of asexual stages and separated male and female gametocytes showed that pb22 is expressed in both asexual stages and gametocytes, while in gametocytes pb22 expression level is about five times higher in female than male gametocytes (Yeoh, Goodman, Mollard, McFadden, & Ralph, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The Ugandan red colobus monkey whole blood transcriptomic dataset was collected by Simons and colleagues (2019) as part of the effort to generate the red colobus monkey reference genome. The sampled individuals ( N = 29) are from a habituated population in Kibale National Park, Uganda, where red colobus have been the subjects of many disease-related studies as a part of the the Kibale EcoHealth Project (Chapman et al, 2005, 2013; Goldberg et al, 2008; Lauck et al, 2011; Simons et al, 2019; Aunin et al, 2020). To identify colobus monkey genes with expression correlated to Hepatocystis parasite levels, we aligned blood transcriptome reads to a concatenated host-parasite pseudo-reference genome (containing genomes of red colobus and Hepatocystis sp.)…”
Section: Resultsmentioning
confidence: 99%
“…At least one species is able to host-switch between primate species (Thurber et al, 2013), but no human infections have been reported. Though nested within the Plasmodium genus as a sister taxon to bat- and rodent-infecting Plasmodium in particular (Galen et al, 2018), Hepatocystis parasites differ in their apparently lack of asexual replication in red blood cells and their use of midges as vectors (Aunin et al, 2020; Garnham, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the predicted cell proportions are available in Supplementary Table 2. To assign parasite life cycle stage, we used a file from Aunin et al [19] which contains single cell CPM-normalised gene expression measurements calculated across 12 different parasite stages taken from Plasmodium berghei. Since this study focuses on the human whole blood transcriptome, only Plasmodium stages within the human blood cell stage were used (male and female gametocyte, trophozoite, ring, merozoite, and schizont stages).…”
Section: Deconvolution Analysismentioning
confidence: 99%
“…As parasite stage can influence gene expression [3,40,41], we deconvoluted the Plasmodium read data through a reference signature gene file from Aunin et al [19]. We found that for both the P. falciparum and P. vivax data, the most predominant stages were early stage circulating forms of the parasite (merozoites and ring stages, Figure 1, A and B).…”
Section: Exploration and Control Of Covariates Influencing Expressionmentioning
confidence: 99%